Exploring older adults' experiences of community-based exercise programs in community nursing interventions: A qualitative study - Qory Tifani Rahmatika; Ronal Surya Aditya; Muhammad Putra Ramadhan; Achmad Masfi (School of Health Sciences Al-Ma'arif, 2026)
Background: The increasing number of older adults is a challenge for public health systems, especially in low- and middle-income countries, because the aging process is often accompanied by a decline in physical function and quality of life in the elderly. Although various studies have shown that community nursing interventions through physical exercise programs have been proven effective, an in-depth understanding of how older adults interpret and directly experience their involvement in these programs is still limited. Objective: This study aims to explore the experiences of older adults who participated in a community-based physical exercise program in Malang City using a qualitative phenomenological approach. Methods: A qualitative phenomenological study was conducted among 24 older adults living in Malang City, Indonesia, who participated in a six-week community-based exercise program. Participants were recruited using purposive sampling. Data were collected through individual, face-to-face, semi-structured interviews conducted in participants’ homes after completion of the intervention. Interviews lasted 30–60 minutes, were audio-recorded with consent, transcribed verbatim, and analyzed manually using thematic analysis. Trustworthiness was ensured through credibility, dependability, confirmability, and transferability strategies, including member checking, field notes, audit trails, and independent coding by two researchers. Results: the data was analyzed thematically and produced four main themes: (i) Rediscovering Physical Capability and Body Confidence, (ii) Exercise as a Meaningful and Enjoyable Social Experience, (iii) Growing Awareness of Health and Self-Care, and (iv) The Community Nurse as a Catalyst for Engagement and Safety. Conclusion: These findings of this study highlight that community nurses play a role not only as instructors but also as facilitators capable of fostering motivation, self-confidence, and sustained participation in older adults through an individual-centered approach. Therefore, nurse-initiated community-based physical exercise programs should be considered for more systematic integration into public health policies as part of strategies to support healthy and sustainable aging.